2016
DOI: 10.1017/jsl.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

On the Symbiosis Between Model-Theoretic and Set-Theoretic Properties of Large Cardinals

Abstract: On the symbiosis between model-theoretic and set-theoretic properties of large cardinals Bagaria, J.; Väänänen, J.A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…In the final chapter of the thesis we study Löwenheim-Skolem theorems for logics extending first-order logic. We extend the work done in [1] by relating upward Löwenheim-Skolem theorems for strong logics to reflection principles in set theory. Finally, we apply our framework to the study of the large cardinal strength of the upward Löwenheim-Skolem theorem for second-order logic; we provide both upper and lower bounds.…”
mentioning
confidence: 99%
“…In the final chapter of the thesis we study Löwenheim-Skolem theorems for logics extending first-order logic. We extend the work done in [1] by relating upward Löwenheim-Skolem theorems for strong logics to reflection principles in set theory. Finally, we apply our framework to the study of the large cardinal strength of the upward Löwenheim-Skolem theorem for second-order logic; we provide both upper and lower bounds.…”
mentioning
confidence: 99%
“…However, Lücke [Lüc21] has established that SR − PwSet is much weaker than SR PwSet . Indeed, he shows 5 In [BV16] it is only assumed that κ witnesses SR − Cd,WC . However, Philipp Lücke [Lüc21] has shown that some additional assumption on κ is needed.…”
Section: Theorem 64 ([Bv16]) If Sr −mentioning
confidence: 99%
“…First, recall that classical work of Magidor in [16] yields a characterization of supercompactness through model-theoretic reflection by showing that second-order logic has a Löwenheim-Skolem-Tarski cardinal (see [5,Definition 6.1]) if and only if there exists a supercompact cardinal. Moreover, Magidor's results show that if these equivalent statements hold true, then the least Löwenheim-Skolem-Tarski cardinal for second-order logic is equal to the least supercompact cardinal.…”
Section: Introductionmentioning
confidence: 99%
“…In order to precisely formulate the relevant results from [2], [3] and [5], we first need to discuss certain subclasses of Σ 2 -formulas defined through standard refinements of the Lévy hierarchy of formulas. Given a first-order language L that extends the language L ∈ of set theory, an L-formula is a Σ 0 -formula if it is contained in the smallest class of L-formulas that contains all atomic L-formulas and is closed under negations, conjunctions and bounded existential quantification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation